Metformin protects against intestinal barrier dysfunction via AMPKα1‐dependent inhibition of JNK signalling activation. Issue 1 (17th November 2017) - Deng, Jun; Zeng, Lishan; Lai, Xueying; Li, Jing; Liu, Le; Lin, Qianyun; Chen, Ye
Abstract: Disruption of the intestinal epithelial barrier, that involves the activation of C‐Jun N‐terminal kinase (JNK), contributes to initiate and accelerate inflammation in inflammatory bowel disease. Metformin has unexpected beneficial effects other than glucose‐lowering effects. Here, we provided evidence that metformin can protect against intestinal barrier dysfunction in colitis. We showed that metformin alleviated dextran sodium sulphate (DSS)‐induced decreases in transepithelial electrical resistance, FITC‐dextran hyperpermeability, loss of the tight junction (TJ) proteins occludin and ZO‐1 and bacterial translocation in Caco‐2 cell monolayers or in colitis mice models. Metformin also improved TJ proteins expression in ulcerative colitis patients with type 2 diabetes mellitus. We found that metformin ameliorated the induction of colitis and reduced the levels of pro‐inflammatory cytokines IL‐6, TNF‐a and IL‐1β. In addition, metformin suppressed DSS‐induced JNK activation, an effect dependent on AMP‐activated protein kinase α1 (AMPKα1) activation. Consistent with this finding, metformin could not maintain the barrier function of AMPKα1‐silenced cell monolayers after DSS administration. These findings highlight metformin protects against intestinal barrier dysfunction. The potential mechanism may involve in the inhibition of JNK activation via an AMPKα1‐dependent signalling pathway.